Application of Montessori-based activities in teaching fractions to intermediate students with learning disabilities - Reyes, Careza P. (2008)
This quasi-experimental design study aimed to find out whether Montessori-based activities and the use of its materials are effective in teaching fractions to intermediate students with learning disabilities. This research used Pre-test and Post-test instruments to gather data. Results revealed that there is a significant difference in the pre-test and post-test scores of the participants after being taught fracations using Montessori-based activities. There was no significant difference between the performance of students with language difficulty and attention difficulty, and the participants' attitude towards the use of the Montessori materials.
Thesis (M.A. Special Education)--University of the Philippines, Diliman.
Keywords: Fraction -- Study and teaching (Elementary) -- Philippines -- Quezon City; Children with disabilities -- Education -- Philippines -- Quezon City; Montessori method of education -- Philippines -- Quezon City; Special education -- Philippines -- Quezon City